The Symbolism of Garden in Armenian Folktales - Vardanyan, Nvard (Bulletin of Yerevan University B: Philology, 2022)
In the rich landscape of a fairy tale, a special place is occupied by the garden as an ideal human habitat - bright, blooming, fertile, with which the motives of love, union, marriage, growth and fertility are associated in the fairy tale.The article deals with the main motives of the fairy tale associated with the garden - their various manifestations - from the paradise garden of immortality to ordinary earthly gardens. The garden is presented as an ideal habitat given to man by God, the misuse of which in some cases leads to the motives for the loss of the garden. The article considers some literary adaptations of these folklore motifs in Armenian and world literature (H.Tumanyan, H.Ch. Andersen, O.Wilde).An attempt is made to clarify the symbolism of the garden in the plots under consideration, to study the problem of the connection between the garden and the singing bird in the context of the semantics of the unity of soul and body.